Rare Species Shift the Structure of Bacterial Communities Across Sphagnum Compartments in a Subalpine Peatland - Tian, Wen; Xiang, Xing; Ma, Liyuan; Evers, Stephanie; Wang, Ruicheng; Qiu, Xuan; Wang, Hongmei (Frontiers in Microbiology, 2020)
Sphagnum-associated microbiomes are crucial to Sphagnum growth and peatland ecological functions. However, roles of rare species in bacterial communities across Sphagnum compartments are poorly understood. Here the structures of rare taxa (RT) and conditionally abundant and rare taxa (CART) from Sphagnum palustre peat (SP), S. palustre ectosphere (Ecto) and S. palustre endosphere (Endo) were investigated in the Dajiuhu Peatland, central China. Our results showed that plant compartment effects significantly altered the diversities and structures of bacterial communities. The Observed species and Simpson indices of RT and CART in alpha diversity significantly increased from Endo to SP, with those of Ecto in-between. The variations of community dissimilarities of RT and CART among compartments were consistent with those of whole bacterial communities (WBC). Network analysis indicated a non-random co-occurrence pattern of WBC and all keystone species are affiliated with RT and CART, indicating their important role in sustaining the WBC. Furthermore, the community structures of RT and CART in SP were significantly shaped by water table and total nitrogen content, which coincided with the correlations between WBC and environmental factors. Collectively, our results for the first time confirm the importance of rare species to bacterial communities through structural and predicted functional analyses, which expands our understanding of rare species in Sphagnum-associated microbial communities in subalpine peatlands.